THE INTRODUCTION OF “FREE, PRIOR AND INFORMED CONSENT” TO THE LAND REFORM LEGAL LEXICON Baleni v Minister of Mineral Resources 2019 (2) SA 453 (GP) - George Barrie (Obiter, 2024)
Although decided four years ago, Baleni v Minister of Mineral Resources (2019 (2) SA 453 (GP) (Baleni)) stands out regarding four significant features and it remains surprising that the decision has not attracted more attention in connection with the land-reform programme. The first feature was the interpretation of the Interim Protection of Informal Land Rights Act 31 of 1996 (IPILRA). The second feature was the emphasis on customary law in the interpretation of IPILRA. The third feature was the application of multiple international-law instruments in the interpretation of IPILRA. The fourth feature was the court’s conclusion that these international-law instruments determine that no decisions may be taken regarding the lands of indigenous peoples without the latter’s “free, prior and informed consent” (FPIC). This conclusion has far-reaching implications for the South African land-reform process introduced by section 25 of the Constitution of the Republic of South Africa, 1996 (the Constitution).